2010
DOI: 10.1111/j.1743-6109.2010.01957.x
|View full text |Cite
|
Sign up to set email alerts
|

Woman and Partner-Perceived Partner Responses Predict Pain and Sexual Satisfaction in Provoked Vestibulodynia (PVD) Couples

Abstract: Introduction. Provoked vestibulodynia (PVD) is a highly prevalent vulvo-vaginal pain condition that results in significant sexual dysfunction, psychological distress, and reduced quality of life. Although some intra-individual psychological factors have been associated with PVD, studies to date have neglected the interpersonal context of this condition. Aim.We examined whether partner responses to women's pain experience -from the perspective of both the woman and her partner -are associated with pain intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
91
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 59 publications
9
91
2
Order By: Relevance
“…Furthermore, the associations were mediated by greater patient and partner pain catastrophizing and self-efficacy [39,40]. In fact, partner pain catastrophizing and selfefficacy directly predicted patient pain, suggesting that the partner's view of the pain may modulate patient symptomatology [41].…”
Section: B Psychosocial Precursors/maintenance Factorsmentioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore, the associations were mediated by greater patient and partner pain catastrophizing and self-efficacy [39,40]. In fact, partner pain catastrophizing and selfefficacy directly predicted patient pain, suggesting that the partner's view of the pain may modulate patient symptomatology [41].…”
Section: B Psychosocial Precursors/maintenance Factorsmentioning
confidence: 92%
“…In fact, partner pain catastrophizing and selfefficacy directly predicted patient pain, suggesting that the partner's view of the pain may modulate patient symptomatology [41]. Lower negative partner responses were also associated with more sexual satisfaction in women, and this association was mediated by greater dyadic adjustment [39,40]. Another study with a sample of 121 couples showed that facilitative partner responses -defined as partner responses that encourage a patient's efforts at adaptive coping with the pain (e.g., decreased avoidance) -were associated with lower vulvovaginal pain and higher sexual satisfaction [42].…”
Section: B Psychosocial Precursors/maintenance Factorsmentioning
confidence: 94%
See 1 more Smart Citation
“…Only one prior study has investigated the association between male partner responses and sexual function -the primary measure of disability in vulvodynia (Rosen et al, 2010). No associations were found between solicitous and negative partner responses and sexual function, and facilitative responses were not assessed.…”
Section: Partner Responses To Pain and Sexual Functioningmentioning
confidence: 99%
“…Further, pain and sexual impairment may be distinct and partially independent phenomena, as evidenced by the lack of significant correlation between pain intensity during intercourse and overall sexual function, as well as pain and sexual satisfaction, in a recent study of women with PVD (Rosen, Bergeron, Leclerc, Lambert, & Steban, 2010). Thus, interpersonal variables may show differing patterns of association with these two possibly unrelated yet critical outcomes.…”
Section: Introductionmentioning
confidence: 99%